Dynamic tribo-pair of PS400 and DLC for planet Venus application. (December 2021) - Tsigkis, Vasilis; Lan, Pixiang; Polycarpou, Andreas A.
Abstract: Bearing materials in future missions to Venus will encounter high temperatures (~462 °C) and extremely dense CO2 atmosphere. Herein, we report on the tribological behavior of PS400 coating (NiMoAl-based alloy) vs. DLC coating at 25, 300, and 500 °C under CO2 and air environments. We found that at 25 °C DLC provides excellent lubrication and extreme wear resistance. At 300 °C in CO2, oxygen-containing terminating groups passivated the dangling bonds of the graphitized DLC, and low friction was maintained. However, under air the friction increased significantly. At 500 °C, DLC was worn out and PS400 transfer oxides alleviated the wear in both environments. The unworn and worn surfaces were analyzed using different analytical techniques. Highlights: DLC provides excellent lubrication at 25 and 300 °C. PS400 provides excellent lubrication at 500 °C. At 300 °C, PS400 vs. DLC exhibits low friction in CO2 but not in air. At 500 °C, PS400 transfer oxides enhance wear performance. PS400 vs. DLC dynamic tribo-pair for Venusian CO2 environment bearing applications.